2020
DOI: 10.1097/yco.0000000000000593
|View full text |Cite
|
Sign up to set email alerts
|

Opioid use and schizophrenia

Abstract: Purpose of review To summarize the current literature regarding comorbid schizophrenia and opioid use disorder (OUD). Recent findings Epidemiological evidence is unclear on whether patients with schizophrenia have a higher rate of OUD. Patients with OUD have been shown to have a higher risk of developing schizophrenia. However, it is clear that patients with both schizophrenia and OUD are less likely to receive standard of care including medication-assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…These 2 conditions share a common mechanism involving the kappa opioid receptor pathway, which is reversable by opioid antagonists. [45][46][47] The opioid receptor pathway is also required to control respiratory syncytial virus replication, thereby controlling its disease severity. 51 Such observations only suggest but do not indicate a specific mechanism of action here and merit further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These 2 conditions share a common mechanism involving the kappa opioid receptor pathway, which is reversable by opioid antagonists. [45][46][47] The opioid receptor pathway is also required to control respiratory syncytial virus replication, thereby controlling its disease severity. 51 Such observations only suggest but do not indicate a specific mechanism of action here and merit further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Separately, PD, SUD, and COVID-19 have been found among people with environmental risks or low socioeconomic status, including persons experiencing homelessness and those with poor medical care . One common pathogenesis pathway proposed is the development of an inflammatory response among those with PD, SUD, or COVID-19 . Substance use can influence the pulmonary, cardiac, metabolic, and immune systems; each such system is also targeted by the SARS-CoV-2 virus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study found a very high co-incidence of PTSD and opioid abuse among women that was explained by a history of childhood trauma (Najavits et al, 1997). The risk for schizophrenia and psychosis is also increased by ELA (van Os et al, 2010;Bentall et al, 2014), which are highly comorbid with substance use disorder (Schmidt L. M. et al, 2011;Li et al, 2020). Palatable food cravings and disordered eating are strongly associated with ELA (Halmi, 2009;Dallman, 2014;Osadchiy et al, 2019), and these cravings are commonly observed in individuals with OUD (Morabia et al, 1989;Pelchat, 2002;Mysels and Sullivan, 2010;Canan et al, 2017;McDonald and Laurent, 2019;Nolan, 2019).…”
Section: Dysfunction Of Reward Circuits: a Common Thread For Oud And mentioning
confidence: 99%
“…high genetic risk, schizotypal personality disorder, subpsychotic symptoms, etc.) [93]. Studies have indicated that this risk is comparable or higher than for cannabis, stimulants and alcohol [94,95].…”
Section: Psychotic Disordersmentioning
confidence: 99%